Maternal consumption of ultra-processed foods and newborn exposure to perfluoroalkyl substances (PFAS) - Nathalia Ferrazzo Naspolini; Priscila Pereira Machado; Josino Costa Moreira; Carmen Ildes Rodrigues Fróes Asmus; Armando Meyer (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Abstract: Evolving evidence shows that ultra-processed food consumption may increase exposure to chemicals used in food packaging and production, such as per- and poly-fluoroalkyl substances, phthalates, and bisphenols. Studies suggested that these contaminants may be transferred from mother to child through placenta, increasing concerns for both maternal and child health. This study aimed to investigate the association of maternal consumption of ultra-processed foods with newborn exposure to perfluoroalkyl substances (PFAS) in the PIPA Project (The Rio Birth Cohort Study on Environmental Exposure and Childhood Development). The pilot cohort study conducted with 131 pregnant women-child pairs in a public maternity school in Rio de Janeiro, Brazil, was assessed. Maternal dietary intake in the third trimester of pregnancy was evaluated using a qualitative food frequency questionnaire. Food items were classified as non-ultra-processed food and ultra-processed food using the NOVA system and regular consumption of ultra-processed foods was estimated. Newborns of pregnant women who weekly consumed three or more subgroups of ultra-processed food presented the highest level of PFAS (2.47ng/mL; 95%CI: 1.22; 3.72), compared to non-consumption of ultra-processed food investigated (0 ultra-processed food = 1.86ng/mL; 95%CI: 1.38; 2.50). Additionally, cluster analysis grouped ultra-processed food, fish, and PFAS levels. In conclusion, we found increased levels of PFAS in newborns whose mothers were higher consumers of ultra-processed foods.